KEMAMPUAN BERBAHASA ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK MEKAR DESA SUKAMULYA KECAMATAN PARINDU KABUPATEN SANGGAU KAJIAN PSIKOLINGUISTIK - Rahmawati, Devi; Syahrani, Agus; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Devi Rahmawati 2023. Research on "Language Ability of Children Aged 5-6 Years in Mekar Kindergarten, Sukamulya Village, Parindu District, Sanggau Regency Psycholinguistic Studies". This study uses qualitative methods in obtaining and analyzing data. The language skills of children aged 5-6 years basically begin with the acquisition of phonology and syntax. In this study, data analysis was based on phonology and syntax. The subjects of this study were children aged 5-6 years who were in Mekar Kindergarten in Sukamulya Village. This study observes the language skills of children aged 5-6 years who have language skills in pronouncing vowel phonemes, consonant phonemes, and sentence patterns. Research resulting from this study shows that children aged 5-6 years are able to speak the pronunciation of vowel phonemes, consonant phonemes, and sentence patterns. However, even though children are already capable of acquiring phonology there are children who experience changes in the sounds that are voiced. In the pronunciation of the word "first" to "daholo", the child (research subject) changed the vowel [u] to [o]. In consonant phonemes children (research subjects) are already able to pronounce consonant phonemes. However, there are children who do discharge in the pronunciation of consonants. In the pronunciation of the word "because" becomes "because" the child (research subject) releases the consonant phoneme [r]. In the acquisition of syntax, children (research subjects) are able to use sentences grammatically.